Oassi sámi noaidevuođa birra Kaspar Peucera čállosis Commentarius de praecipuis divinationum generibus (Wittenberg 1560): Teakstakritihkalaš hámis jorgalusain ja kommentáraiguin - Aspaas, Per Pippin; Gaski, Harald (Nordlit, 2014)
The text on Sami shamanism in Caspar Peucer’s Commentarius de praecipuis divinationum generibus (Wittenberg 1560): Critical edition, with translation and commentary. Among the sources dealing with the shamanistic skills of the Sami (formerly Lapponian) population, a certain text by Kaspar Peucer has so far been little known. This man of extreme learning was the son-in-law of Philip Melanchthon and a Professor at the University of Wittenberg. A true polyhistor, well versed in Medicine, Geography, Astrology, Theology, etc., Peucer included in his chef-d’oeuvre on divination an elaborate description of the shamanism of the so-called Pilappii. The present article offers a critical edition of this text, based on the editions of Wittenberg 1560 (A), 1572 (B), 1580 (C), as well as Zerbst 1591 (D) and Frankfurt 1593 (E). In addition to translations into North Sami and Norwegian (see Appendix), some contextualisation is offered, which can be summarised as follows: A similar testimony on shamanism is found in the Historia de gentibus Septentrionalibus by Olaus Magnus (Rome 1555). However, that text is not elaborate enough to prove that Kaspar Peucer has copied his description from him. It is more likely that some student among the considerable number of Swedes, Finns and Norwegians that were immatriculated at Wittenberg University in the years following the Reformation, presented this account to Peucer. Many details in the account make it strikingly similar to Sami folk narratives that have been assembled several centuries later. For example, the description of maritime Sami by Anders Larsen (1870–1949), the Sami book by Johan Turi (published 1910) and Sami songs (joik) that were collected by Jacob Fellman in the 1820’s can be compared with Peucer’s account. Peucer himself, however, categorised the shamanism of the Sami as a form of theomanteia, i.e. a form of magic which he considered to originate not from the true God, but from the Devil.